Behavioural effects of high fat diet in a mutant mouse model for the schizophrenia risk gene neuregulin 1. (17th February 2016) - Holm‐Hansen, S.; Low, J. K.; Zieba, J.; Gjedde, A.; Bergersen, L. H.; Karl, T.
Abstract : Schizophrenia patients are often obese or overweight and poor dietary choices appear to be a factor in this phenomenon. Poor diet has been found to have complex consequences for the mental state of patients. Thus, this study investigated whether an unhealthy diet [i.e. high fat diet (HFD)] impacts on the behaviour of a genetic mouse model for the schizophrenia risk gene neuregulin 1 (i.e. transmembrane domain Nrg1 mutant mice: Nrg1 HET). Female Nrg1 HET and wild‐type‐like littermates (WT) were fed with either HFD or a control chow diet. The mice were tested for baseline (e.g. anxiety) and schizophrenia‐relevant behaviours after 7 weeks of diet exposure. HFD increased body weight and impaired glucose tolerance in all mice. Only Nrg1 females on HFD displayed a hyper‐locomotive phenotype as locomotion‐suppressive effects of HFD were only evident in WT mice. HFD also induced an anxiety‐like response and increased freezing in the context and the cued version of the fear conditioning task. Importantly, CHOW‐fed Nrg1 females displayed impaired social recognition memory, which was absent in HFD‐fed mutants. Sensorimotor gating deficits of Nrg1 females were not affected by diet. In summary, HFD had complex effects on the behavioural phenotype of test mice and attenuated particular cognitive deficits of Nrg1 mutant females. This topic requires further investigations thereby also considering other dietary factors of relevance for schizophrenia as well as interactive effects of diet with medication and sex. Abstract : High fat diet improves social recognition memory deficits of Nrg1 mutant mice.